2018
DOI: 10.1136/bmjpo-2018-000287
|View full text |Cite
|
Sign up to set email alerts
|

Antacid therapy for gastroesophageal reflux in preterm infants: a systematic review

Abstract: BackgroundGastro-oesophageal reflux is prevalent in preterm infants. Despite widespread use in clinical practice, there is still much controversy over the efficacy and safety of drug interventions, particularly antacid therapy.ObjectiveTo systematically review the effects of antacid therapy on preterm infants with symptoms of gastro-oesophageal reflux, and to assess the safety of these interventions.MethodsWe carried out an electronic search of the Cochrane central register of controlled trials (CENTRAL, The C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…GOR is a prominent condition among preterm infants. Symptoms such as apnoea, bradycardia, vomiting, poor weight gain and irritability have been attributable to GOR, which is called gastroesophageal reflux disease (GORD), when symptoms are severe [15]. Experimental data showed that L. reuteri can promote gastric motility, accelerate gastric emptying, promote colonic peristalsis, and reduce the incidence of dyspepsia and reflux [16, 17].…”
Section: Discussionmentioning
confidence: 99%
“…GOR is a prominent condition among preterm infants. Symptoms such as apnoea, bradycardia, vomiting, poor weight gain and irritability have been attributable to GOR, which is called gastroesophageal reflux disease (GORD), when symptoms are severe [15]. Experimental data showed that L. reuteri can promote gastric motility, accelerate gastric emptying, promote colonic peristalsis, and reduce the incidence of dyspepsia and reflux [16, 17].…”
Section: Discussionmentioning
confidence: 99%
“…Medicines utilization research informs us on trends, on between unit variability and on the impact of guideline implementation. This utilization research is not limited to exposure to antibiotics [ 4 , 9 , 10 , 11 , 12 , 13 , 14 , 20 ], but has been illustrated using data on drugs for gastroesophageal reflux, analgesics or anti-epileptic drugs [ 4 , 17 , 18 , 19 , 20 , 21 ]. We hereby illustrate how a shift in practices can result in another irrational practice with another compound (shift from prokinetics to anti-acid drugs to treat reflux associated-apnea).…”
Section: Discussion: Perspectives To Further Improve Rational Use mentioning
confidence: 99%
“…This occurred despite the lack of evidence that gastric acid reducing drugs are effective to reduce gastric acid production, reflux and apnea. More recently and following this shift, there was also emerging evidence on relevant harm (higher incidence of necrotizing enterocolitis or late onset sepsis) [ 17 , 19 ].…”
Section: Neonatal Clinical Pharmacologymentioning
confidence: 99%
“…When regurgitation occurs it is recommended to sit upright or raise the head of the preterm during the feeding and for at least 60 minutes after feeding (McGill-Vargas & Ilg, 2018). Symptoms such as vomiting, poor weight gain, intolerance and irritability have been attributable to regurgitation in preterm infants (Dermyshi, Mackie, Kigozi, Schoonakker & Dorling, 2018). Dermyshi, etal.…”
Section: Introductionmentioning
confidence: 99%